Pharmacokinetics and exposure-efficacy relationships of omalizumab in patients with nasal polyps. (December 2021) - Zhu, Rui; Owen, Ryan; Wilkins, Justin; Schoemaker, Rik; Tian, Xianbin; Gautier, Aurelie; She, Gaohong; Vadhavkar, Shweta; Cheu, Melissa; Wong, Kit; Omachi, Theodore A.; Putnam, Wendy S.; et al.
Abstract: The anti-immunoglobulin E (IgE) antibody, omalizumab (Xolair), is approved in the United States for the treatment of allergic asthma and chronic spontaneous urticaria, and has recently been studied for the treatment of nasal polyposis following completion of the two replicate phase 3 studies (POLYP 1 and POLYP 2). The dosing of omalizumab used in the phase 3 studies is based on a combination of patients' pre-treatment IgE level and body weight, similar to the approach used in allergic asthma. The objectives of the current analyses were to evaluate whether the pharmacokinetics (PK) of omalizumab and its pharmacodynamic (PD) effect on free and total IgE level in chronic rhinosinusitis with nasal polyps (CRSwNP) are consistent with those in allergic asthma via population PK/PD modeling and simulation, and to graphically explore exposure-response relationships and free IgE-response relationships in CRSwNP. Omalizumab PK and PD effect of total and free IgE in CRSwNP are generally consistent with those in asthma. Observed post-treatment free IgE suppressions were generally within the target range of the baseline IgE- and body weight-based omalizumab dosing table, with 74.2% and 93.0% of patients achieving a serum free IgE level below 25 ng/mL and 50 ng/mL, respectively at Week 24. Exposure-response analyses indicated that there was no clear correlation between omalizumab or free IgE concentration and key efficacy endpoints within the POLYP studies. Overall, these results indicate that the body weight and IgE-based dosing regimen of omalizumab was appropriate for use in CRSwNP patients.